Central administration of galanin N‐terminal fragment 1–15 decreases the voluntary alcohol intake in rats. (6th December 2017) - Millón, Carmelo; Flores‐Burgess, Antonio; Castilla‐Ortega, Estela; Gago, Belén; García‐Fernandez, María; Serrano, Antonia; Rodriguez de Fonseca, Fernando; Narváez, José Angel; Fuxe, Kjell; Santín, Luis; Díaz‐Cabiale, Zaida
Abstract: Alcohol consumption is considered a major risk factor for disease and mortality worldwide. In the absence of effective treatments in alcohol use disorders, it is important to find new biological targets that could modulate alcohol consumption. We tested the role of the N‐terminal galanin fragment (1–15) [GAL(1–15)] in voluntary ethanol consumption in rats using the two‐bottle choice paradigm as well as compare the effects of GAL(1–15) with the whole molecule of GAL. We describe for the first time that GAL(1–15), via central mechanisms, induces a strong reduction in preference and ethanol consumption in rats. These effects were significantly different than GAL. GAL receptor (GALR) 2 was involved in these effects, because the specific GALR2 antagonist M871 blocked GAL(1–15) mediated actions in preference and ethanol intake. Importantly, the mechanism of this action involves changes in GALR expression and also in immediate‐early gene C‐Fos and receptors‐internalization‐related gene Rab5 in the striatum. The relevance of the striatum as a target for GAL(1–15) was supported by the effect of GAL(1–15) on the locomotor activity of rats after ethanol administration. These results may give the basis for the development of novel therapeutics strategies using GAL(1–15) analogues for the treatment of alcohol use disorders in humans. Abstract : The N‐terminal fragment GAL(1–15) induces a strong reduction in preference and ethanol consumption in rats. The mechanism of this action involves changes in striatum in GAL receptors expression and also in immediate‐early gene C‐Fos and receptors‐internalization‐related gene Rab5.